Rauwolfia Serpentina: A Comprehensive Phytochemical Study of Its Bioactive Metabolites - Mukesh Chander (Emerging Trends in Metabolites, 2024)
Rauwolfia Serpentina is an important medicinal plant used in Ayurveda, Unani, and folk medicine system of medicine. This plant grew as a bush in company of other plants as an evergreen structure. It is commonly known as ‘Sarpaghanda’. in Ayurvedic and Unani medicine system. It is safe and effective for the treatment of snakebites and various types of disease like malaria, breast cancer, prostate cancer, high blood pressure, insomnia, epilepsy, and traumas. Its therapeutic properties are associated with the presence of various phytochemical compounds such as alkaloids, phenols/polyphenols, saponins, tannins, yohimbine and reserpine. Additionally, these bioactive molecules possess remarkable hypoglycemic, anti-diarrheal, anti-bacterial, and anxiolytic properties. R. serpentina known as the Indian snakeroot in ayurvedic system of medicine. It has been used as a very important distinctive medicinal shrub for a long time. The different parts of R. serpentina have bioactive phytochemicals beneficial in controlling human disease like insomnia, insanity, anxiety, sleeplessness, high blood pressure and various other cardiovascular disease affecting human beings. However, the concentration of different phytochemicals varies in root, stem, bark, berry, and leaves of R. serpentina. It may prove to be an “all in one” cure for various human ailments. It has now been cultivated throughout the India and has a wide application in the traditional system of homeopathic medicine also for curing human diseases. It is available as powder, tablet, capsule and liquid syrups and alcoholic dilutions in various herbal formulations available in the market belonging to this plant.
Keywords: Alkaloids; Rauwolfia serpentina; anti-bacterial anxiolytic; anti-diarrheal; anti-hypertensive activity